Novel use pattern of pendimethalin for annual ryegrass (Lolium rigidum Gaudin) control in wheat and barley - Mahajan, Gulshan; Chauhan, Bhagirath S. (Frontiers in Agronomy, 2024)
Annual ryegrass (Lolium rigidum Gaudin) is a problematic weed in most of the crop-ping regions in Australia. Evolved herbicide resistance to multiple mode of action groups, lack of new herbicidal molecules, and the emergence of late cohorts in winter season crops necessitate the use of existing herbicides in an innovative way to control L. rigidum. Pendimethalin as preemergence (PRE) is used for L. rigidum control; however, it is unable to control late cohorts of L. rigidum in winter season crops. Pot studies were conducted from 2019-2021 to evaluate the effect of a post-emergence (POST) application of pendimethalin on L. rigidum control in addi-tion to crop safety in wheat, barley, and sorghum. POST application of pendimethalin was found to be safe for wheat and barley and the biomass reduction in both crops at varied rates (220 to 3520 g ha-1) of pendimethalin ranged from 10-20%. A dose-response study revealed that the pendimethalin dose required for 50% mortality and growth reduction of L. rigidum was 179 and 144 g ai ha-1, respectively. Pendi-methalin at 880 g ai ha-1 completely killed late cohorts of L. rigidum. These results suggest that the POST application of pendimethalin can be used for effective control of late cohorts of L. rigidum in wheat and barley crops. POST-application of pendi-methalin suppressed the biomass of sorghum plants compared with the nontreated control treatment, biomass reduction in sorghum at different pendimethalin doses ranged from 32-40%. Results implied that POST applications of pendimethalin in wheat and barley can diversify herbicide programs in managing L. rigidum and may help in delaying the evolution of resistance in this weed.